Evaluation of the Implementation of Family Planning and Reproductive Health Programs in KB Village, Subang Regency: Case Study of Kalijati District - Ayu Arifianingsih (Journal of World Science, 2025)
The Kampung KB (Family Planning Village) program aims to improve the coverage of family planning (KB) and reproductive health through a community-based approach. Evaluation is needed to determine the extent to which the program is running according to target. To evaluate the implementation of family planning and reproductive health programs in Kampung KB Kalijati District, Subang Regency. Qualitative research with a case study approach. Data were collected through in-depth interviews, field observations, and document review from 30 informants (family planning cadres, family planning acceptors, community leaders, and health center officers). Data analysis used the Miles and Huberman interactive model. The Kampung KB program has succeeded in increasing the number of active family planning acceptors by 20% in the last 2 years. The main obstacles are the limited number of[A1] extension workers, low male participation, and access to reproductive health services in remote areas. Education and cross-sector support still need to be strengthened. The Kampung KB program in Kalijati District is running quite well, but it requires increased human resource support, continuous education, and equitable access to reproductive health services.